Trimetazidine effects on mitochondria energetic activity - S. V. Eliseeva; S. V. Grachev; N. D. Egorova; M. G. Glezer; E. I. Astashkin (Кардиоваскулярная терапия и профилактика)
Aim. To investigate how trimetazidine (TMZ) directly affects oxidative phosphorylation in intact mitochondria (MCH), isolated from the animals not undergoing ischemia-reperfusion process.Material and methods. Rat liver MCH were isolated by standard methods. Oxidative and phosphorylating MCH functions were studied by polarigraphic methods. TMZ was used in the concentrations of 10-4 М and 10-5 М.Results. TMZ in concentrations of 10-4 М and 10-5 М decreased the time of added adenosine diphosphate (ADPH) phosphorylation, reduced the amount of oxygen (O2) necessary for this phosphorylation, and increased ADPH/O2 coefficient. Therefore, phosphorylation velocity and effectiveness increased, i.e. O2 use became more economical, and ATPH synthesis increased. TMZ also increased breath control, which pointed to oxidation and phosphorylation association. TMZ per se did not separate these two processes.Conclusion. MCH energetic function improvement is one of the key factors in TMZ cytoprotective effects.